Conquest of Cyprus by the Turks: Divergence of the Early Modern Period and Establishment of Status Quo in the Mediterranean - Emrah NAKİ (Gazi Akademik Bakış)
The victory of the Ottomans at Djerba (1560) and the Great Siege of Malta (1565) were perceived as a serious threat to the West and led the Pope to mobilize the Catholic states to build an alliance against the Ottomans. Although the Malta siege was fended off successfully by the West, it was obvious that the Ottomans would continue their expansion in the Mediterranean. The toppling in 1570 by the governor of Algeria, Uluç Ali Paşa, of the ruler of Tunisia, a vassal of Spain, and his open support for the Morisco revolts in Spain, was the best proof of it. In the face of Ottoman expansion, it did not appear easy to build an alliance which would counter the Turks both on sea and land by incorporating also the Habsburgs’ Austrian branch, but at least a Christian fleet could be formed led by Spain and Venice. In this respect, Spain, ruled by Philip II, would obviously not oppose it. The real issue for the Pope was to convince the Republic of Venice, which had a large fleet in terms of sea power. Venice, using its commercial relations with the Ottomans as an excuse, initially opposed the Pope’s proposal. However, in the summer of 1570 after the Ottomans had commenced their siege of Cyprus, which was under the domination of Venice, this time it was the Venetians who came up with the proposal of an alliance. Eventually, a Christian alliance (the Holy League) was formed in order to save Cyprus first of all and then to ensure that the Ottomans would no longer be a threat to the West in the Mediterranean. While this study was prepared comparatively from both Turkish and Western sources, rather than describing the anatomy of a war, it examines the relative causes leading to the conquest of Cyprus and their effects.